THE IMPLEMENTATION OF CHARACTER EDUCATION IN ELECTRONIC LEARNING (E-LEARNING) USING GOOGLE CLASSROOM MEDIA OF STKIP PGRI SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
This study discusses how the application of character education in electronic learning (Elearning). Distance education is currently being carried out due to the COVID-19 pandemic. The media used in this research is learning media with google classroom. This research is a descriptive study, the instruments used in this study are observation sheets, questionnaire sheets and test sheets. The character instilled in students here is responsibility, courtesy, respect for other people's opinions, honest and independent. The object of this research is the students of the STKIP PGRI West Sumatra BP 2018 economic education study program with classes D, E and F, totaling 65 people in the economic learning outcome assessment course. The application of character education is very influential in its application in the learning process, because in every learning norm values can be instilled in each individual, even though the implementation of this learning uses distance learning , the essence of learning is from an individual process to become better. With the use of Google Classroom learning media that researchers can apply character education to students, and get good results